2016
DOI: 10.1039/c5nj03244j
|View full text |Cite
|
Sign up to set email alerts
|

Interactions of copper(ii) and zinc(ii) with chlorophyll: insights from density functional theory studies

Abstract: The most favored reaction of chlorophyll is computed to be substitution for Cu2+ and peripheral chelation for Zn2+.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 69 publications
4
14
0
Order By: Relevance
“…Info. ), and in line with our previous studies [31,32], we focused only on the Q y transition. A blue shift is observed when going from Mg to metals of line 4.…”
Section: Electronic Propertiesmentioning
confidence: 59%
See 3 more Smart Citations
“…Info. ), and in line with our previous studies [31,32], we focused only on the Q y transition. A blue shift is observed when going from Mg to metals of line 4.…”
Section: Electronic Propertiesmentioning
confidence: 59%
“…Calculations were based on a Chla model containing 73 atoms reported in Scheme 1 which was proposed in our previous work [31,32,[39][40][41]. This model retains the structure of Chla except for the phytyl ester side chain which was replaced by a methyl group to reduce the number of atoms for computation.…”
Section: Computational Detailsmentioning
confidence: 99%
See 2 more Smart Citations
“…We state, therefore, similarly to other authors who showed the formation of metal-chlorophyll complexes that cadmium eliminates magnesium from chlorophyll and replaces it in the central position of the porphirine ring. Many papers on metaloporphirins have been published (Kang et al 2018;Bechaieb et al 2016b;Zvezdanović et al 2014;Küpper et al 2006). Recently, based on quantum chemical calculations (with Gaussian 09 program, using the density functional theory DFT at B3LYP level) the chemical structures of metaloporphirins (with Hg, Pb and Cd) were described and the reaction of metaloporphirin formation was postulated (Bechaieb et al 2016a).…”
Section: Absorption and Fluorescence Characteristics Of Chlorophyll Dmentioning
confidence: 99%